Self-stigmatization of high-school students seeking professional psychological help: the chain-mediating effect of perceived social support and optimism - Bu, Nanyin; Li, Zuoshan; Jiang, Jiarui; Chen, Xin; Li, Ziying; Xiao, Yujuan; Wang, Xueyan; Zhao, Tianyi (Frontiers in Psychiatry, 2023)
Background: Research has shown that stigmatization of professional psychological help-seeking is an important factor influencing attitudes toward seeking professional psychological help (ATSPPH). However, how perceived social support (PSS) and optimism have a mediating role is not clear. Objective: Examine the associations between ATSPPH, self-stigmatization of seeking help, PSS, and optimism in a cohort of Chinese high-school students (HSSs). Methods: An offline survey was conducted in three high schools in Chongqing (China) from 20 February to 20 May 2023. Participants were HSSs recruited through their teachers. A total of 2,159 HSSs completed a survey on demographic information as well as the Self-Stigmatization of Seeking Help (SSOSH) score, ATSPPH, Perceived Social Support Scale (PASS), and Life Orientation Test(LOT). Mediation analyses were conducted using the "Process" macro in SPSS 26.0 to estimate the direct and indirect effects of self-stigmatization of seeking psychological help on ATSPPH. Results: Self-stigmatization of seeking psychological help was significantly and negatively related to ATSPPH among HSSs. Self-stigmatization of psychological help-seeking influenced ATSPPH through three pathways: (a) separate mediating effect of PSS (effect = −0.029); (b) separate mediating effect of optimism (effect = −0.069); (c) chain-mediating effect of PSS and optimism (effect = −0.017). These data suggested that self-stigmatization of psychological help-seeking could influence ATSPPH directly and indirectly through PSS and optimism. Conclusions: PSS and optimism mediated the relationship between self-stigmatization of seeking help and ATSPPH. Improving the ability of HSSs to perceive social support and cultivating optimism could help improve the self-stigmatization of help-seeking and promote a positive attitude towards professional help-seeking.